If f(x)=4/3x-9 what is f^-1(-3)
1 answer:
9514 1404 393
Answer:
4.5
Step-by-step explanation:
The value of x that makes f(x) = -3 is ...
4/3x -9 = -3
4/3x = 6 . . . . . . add 9
x = 6(3/4) = 18/4 = 9/2 = 4.5 . . . . multiply by 3/4
f^-1(-3) = 4.5
You might be interested in
Answer:
190.28in
Step-by-step explanation:
Sides= 31.2
Front and back= 58.2
Top and bottom= 100.88
Add them together= 100.88+58.2+31.2
Answer: 2
Step-by-step explanation: subtract by 2 every time.
Answer:
exact: X=53/5
decimal: X=10.6
mixed number form: X= 10 3/5
Step-by-step explanation:
Answer:
y = x -7
Step-by-step explanation:
y2 - y1 / x2 - x1
-5 - (-2) / 2 - 5
-3/-3
1
y = x + b
-2 = 5 + b
-7 = b
y = -7
y = x -7
Answer:
D) 240 000 cm³
Step-by-step explanation:
V = 100cm×80cm×(80-50)cm
= 8000cm²×30cm
= 240 000 cm³